The impact of public health control measures during the SARS epidemic in mainland China. - de Vlas, S; Feng, D; Cooper, B; Fang, L; Cao, W; Richardus, J (2009)
We tracked the effective reproductive number (Rt) over time to assess the impact of important public health control measures in the five most SARS-affected geographic areas in mainland China. As soon as the Chinese authorities gained full control of all activities to combat SARS, Rt decreased dramatically and consistently below one. Many control measures that seriously affected public life were implemented afterwards, i.e., when the epidemic was already dying down.